Prinsip-Prinsip Etika Kristen dan Implementasinya bagi Transformasi Kebijakan dan Pelayanan Publik di Indonesia - Wong, Fingfing Keren Grace; Senjaya, Styadi (Institut Agama Kristen Negeri Manado, 2024)
This research aims to explore how Christian ethical principles can be applied in public policy and services in Indonesia. This research method uses a qualitative approach with literature study. The research results identified seven principles of Christian ethics that are relevant for the Indonesian context, namely: love, mercy, truth, justice, loyalty, integrity, and service. Also explains several examples of the application of Christian ethical principles in several fields such as health, education, environment, and anti-corruption. The conclusion of the discussion states that Christian ethical principles can contribute to the transformation of public policy and services in Indonesia.